A switched‐beam millimeter‐wave array with MIMO configuration for 5G applications. Issue 4 (8th March 2018) - Ikram, Muhammad; Sharawi, M. S.; Klionovski, K.; Shamim, A.
Abstract: In this work, a switched‐beam 2‐element multiple‐input multiple‐output (MIMO) antenna system is proposed at mm‐wave bands for 5G applications. The antenna system consists of a 4 × 4 connected slot antennas for each MIMO element forming the connected antenna array (CAA). A feed network based on a Butler matrix is used to excite the CAA, in addition to steer the beam at different locations which enhance the diversity performances. The mm‐wave MIMO antenna system operates at 28 GHz with at least −10 dB measured bandwidth of 830 MHz (27.4 GHZ–28.23 GHz). It is fabricated on a commercially available RO3003 substrate with dielectric constant of 3.3 and height of 0.13 mm, respectively. The dimensions of the board are equal to 150 mm 3 × 100 mm 3 × 0.13 mm 3 . The proposed design is compact, low profile, and suitable for future 5G‐enabled tablet PCs.